Analisis informasi akuntansi diferensial dalam pengambilan keputusan investasi pada perluasan jaringan pipa PDAM Kabupaten Minahasa Utara - Mitzy, Mitzy; Saerang, David P. E.; Pinatik, Sherly (Manajemen Bisnis dan Keuangan Korporat, 2025)
The expansion of the pipe network is a significant investment decision for the North Minahasa District Water Company (PDAM) in its efforts to improve clean water services for the community. Differential accounting information refers to data that compares relevant costs and revenues between investment alternatives to facilitate better decision-making. This study aims to analyze how differential accounting information can be utilized to support investment decisions related to the expansion of the pipeline network at the PDAM. A qualitative research method with a descriptive approach was employed. The results indicate that differential accounting information assists management in identifying relevant costs and revenues, as well as evaluating the feasibility of the available investment options. Therefore, differential accounting information can serve as a valuable analytical tool to support investment decisions concerning pipeline network expansion at the PDAM.